Pengaruh Pembiayaan dengan Akad Murabahah terhadap Tingkat Profitabilitas Bank di Kantor Cabang Bank Syariah Indonesia Kabanjahe - Sofiyah Montase Siregar; Khairina Tambunan (Regress: Journal of Economics & Management, 2021)
This study investigates the impact of murabahah financing on bank profitability at Bank Syariah Indonesia Kabanjahe Branch in response to the need to evaluate the performance of Islamic financing instruments within competitive financial markets. The research problem addresses whether murabahah-based financing significantly influences the profitability level of the bank. Using a quantitative approach, the study analyzes customer financing data from 2019 to 2021 through normality testing, multicollinearity analysis, multiple linear regression, and t-tests. The empirical results demonstrate a statistically significant and positive relationship between murabahah financing and bank profitability, indicating that higher volumes of murabahah financing contribute to improved financial performance. These findings confirm the strategic role of murabahah as a dominant profit-generating instrument in Islamic banking operations. The study concludes that strengthening murabahah financing portfolios can enhance the profitability and financial sustainability of Islamic banks, particularly at the branch level, while reinforcing the effectiveness of Sharia-compliant financing mechanisms in supporting institutional growth.